Assessment of cultural fit between buyers and suppliers. Issue 4 (24th February 2020) - Patyal, Vishal Singh; Ambekar, Sudhir; Prakash, Anand; Roy, Dipayan; Hiray, Amit
Abstract : Purpose: The present study proposes a model to examine the cultural fit between buyers and suppliers for establishing synergies in their processes and practices. Design/methodology/approach: This study assessed buyers' culture through the Competing Values Framework and used Quality Management Practices Model as a proxy to assess suppliers' culture. The data from 262 paired respondents were used for this analysis. This survey was administered in India, using linear snowball-sampling technique. This study applied 3SLS regression for each culture group separately. Findings: This study has instituted the cultural fit between the buyers' and suppliers' culture. It is observed that for getting synergies between cultures, buyers need to choose a set of suppliers which have similar cultural traits. Research limitations/implications: This study presents empirical findings based on data from Indian manufacturing firms. These findings need testing in other developing countries and other sectors. Practical implications: Organizations can formulate right policies for supplier selection based on the cultural fit between buyers and suppliers. Originality/value: With increasing role of suppliers in the value chain, organizations around the world need to work with the right suppliers for gaining a sustainable competitive advantage. Selection of the right suppliers depends on the cultural fit between buyers and suppliers that, in turn, depends on the selection of the right suppliers based on the prevailing culture.